Active saponins from root of Pueraria peduncularis (Grah. ex Benth.) Benth. and their molluscicidal effects on Pomacea canaliculata. Issue 6 (27th October 2016) - Yang, ChunPing; Zhang, Min; Lei, Bo; Gong, GuoShu; Yue, GuiZhou; Chang, XiaoLi; Sun, XiaoFang; Tian, Yue; Chen, HuaBao
Abstract: BACKGROUND: Pueraria peduncularis (Grah. ex Benth.) Benth., which belongs to the Leguminosae family, exhibits resistance to many crop pests in agricultural production. Pomacea canaliculata is an important invasive snail in rice fields and causes severe yield losses. To evaluate the toxicity of P. peduncularis to P. canaliculata, in this study the molluscicidal activity of root extracts of P. peduncularis was tested against P. canaliculata ; the active compounds were isolated, and the structures of these compounds were analysed using nuclear magnetic resonance (NMR) analysis and mass spectral analysis. RESULTS: Our results showed that the molluscicidal activity of the root crude extract differed between P. canaliculata with different shell diameters after treatment for 72 h. The median lethal concentration (LC50 ) was 5.511 mg L −1 against snails of 1.5 ± 0.2 cm diameter and 12.383 mg L −1 against snails of 2.5 ± 0.2 cm diameter. Furthermore, two active ingredients isolated from root methanol extracts were identified as pedunsaponin A and pedunsaponin C. Both pedunsaponin A and pedunsaponin C showed strong molluscicidal activities, with LC50 values of 3.893 and 4.252 mg L −1, respectively, against snails with shell diameters of 1.5 ± 0.2 cm after treatment for 72 h. CONCLUSION: Pueraria peduncularis extracts exhibit high molluscicidal activity and have great potential value for exploring a molluscicide to control Pomacea canaliculata . © 2016 Society of Chemical Industry